Otimização da produção de lipase e celulase por fermentação submersa utilizando a torta da polpa e fungos isolados do fruto da macaúba (Acrocomia aculeata) - Camila Sales Nascimento (2015)
Research into the selection of suitable substrates for the fermentation process has mainly been focused on agro-industrial waste, because to its potential advantages. Use them as raw material for the production of enzymes it has become viable because of its low cost, its high availability and resolution of related pollution problems. Thus, this work had as focus, study the production of enzymes lipases and cellulases by filamentous fungi isolated from the fruit of Macaúba (Acrocomia aculeata) by submerged fermentation process, using as substrate cake residual from oil extraction process of the pulp Macaúba. Nineteen filamentous fungal isolates of the fruit have been evaluated quantitatively for the production capacity of lipase, cellulase and protease. Fusarium proliferatum M62, Fusarium sp. M184, Fusarium sp.M233, Cladosporium cladosporonoides M19, Fusarium proliferatum M62, Penicillium sp. M89, Fusarium sp. M184 and Fusarium sp. M233 were positive for lipase, cellulase and protease activity. The isolate Penicillium sp. M89 has been the best simultaneously lipase and cellulase producer, following with the optimization tests of fermentation medium containing Macaúba cake. First, was performed a Factorial Design of Mixed Levels L12, the results indicated that the variables, Macaúba cake concentrations and type of nitrogen source, significantly influenced (<0.05) the lipolytic activity, while the temperature variable influenced (<0.05) the cellulase activity. Next, in the Rotational Central Composite Design, the results have allowed stipulate the optimal conditions of simultaneous production of the two enzymes tested. Results allowed to stipulate the optimal conditions of simultaneous activity of the two enzymes tested, for the activity of enzymes in UmL-1, the best condition was 3.5% Macaúba cake and 33.7ºC. For the enzymatic activity Umg-1, the best condition was 2.5% Macaúba cake and 34.4ºC temperature and for the enzymatic activity in Ug-1 optimal conditions was 2.5% Macaúba cake and 40°C. The optimization resulted in activity increasement of enzymes. The research conducted generated perspectives of new studies associated to the use of Macaúba cake for production hydrolases by low cost processes